Desarrollo del pensamiento critico-reflexivo y la creatividad a través de las ciencias naturales (1996)
ABSTRACT:This work was done at Lucrecio Jararuillo Vólez school in Medcllin city, with students of seventh grade in the sccond semester in 1995, and with students of sixth and eight grade in the first triinester in 1996. Dnring ttiis time thcy practiccd the strategies of the project "PRYCRLA” in 35 sessions distributed so: 15 C.I, 6 I.C.C., 8 A.T.A. and six axises of free creation in the area of natural Science. Furthermore they practiced interviews to students and teachers, they applied inquest to students, director and teacher. They were done two videos Ihat they show the competence with the mind in parallels groups about the themes involved in the narrations elaborated in the sessions of the axis of free creation. Tlris work was elaborated in environment of ihoughiful dialogue where the teacher assumed the role to facilitale the process and the students constituted the central axis of the act to learn), making and understanding. As gathering instrment of evidente they employed the students notebooks, rccording, inquest, interview, notes of finish sessions, questionnaire, reports to the teachers and directors and advisor reports. To rank the session they were selected the categories: argument, inquest, mental aperture, and creation and as subcategories: C.I., I.C.C., A.T.A., and axis of free creation. They were realized eight graphes they get back the comportmenf of difierent categories and attitudes that were observed through the process. this work has as a purpose to evidence the comportmenl of the students in front, of the strategies of the project “PRYCREA” with the intention to search the development the skills of the thought, the profit of apprenticeship signiticant and a stimulation of the students toward the motivation intrinsic, with the purposc to raise the academic level and to contribute to formalion of a citizen apt to live in the society.